Symptom‐based management of the idiopathic interstitial pneumonia. Issue 8 (9th October 2015) - Garibaldi, Brian T.; Danoff, Sonye K.
Abstract: The term 'idiopathic interstitial pneumonia' (IIP) encompasses a wide variety of diseases with different and often unexplained pathophysiology as well as diverse natural histories. Unfortunately, many of these diseases are progressive and some are poorly responsive to available therapies. Despite the varied nature of IIPs, patients experience common symptoms related to their chronic lung disease. Dyspnoea, cough, fatigue and depression contribute substantially to morbidity and are often difficult to manage. The psychological stress of having a chronic and often life‐limiting disease further complicates symptom control. Effective symptom‐management requires a multidisciplinary approach that incorporates patient education and self‐management to formulate goals of care and treatment plans. In this context, palliative care is incorporated from the time of diagnosis of an IIP and is not restricted to the end stages of the disease. Pulmonary rehabilitation plays a central role in symptom‐management and has beneficial effects across multiple domains. In patients who do not respond to disease‐specific treatments and are not candidates for lung transplant, early referral to hospice may improve quality of life for both patients and their families near the end of life.